Cognitive behavioral therapy for insomnia has sustained effects on insomnia, fatigue, and function among people with chronic heart failure and insomnia: the HeartSleep Study. Issue 1 (17th October 2021) - Redeker, Nancy S; Yaggi, Henry Klar; Jacoby, Daniel; Hollenbeak, Christopher S; Breazeale, Stephen; Conley, Samantha; Hwang, Youri; Iennaco, Joanne; Linsky, Sarah; Nwanaji-Enwerem, Uzoji; O'Connell, Meghan; Jeon, Sangchoon
Abstract: Study Objectives: Insomnia is common among adults with chronic heart failure (HF) and associated with daytime symptoms and decrements in function. The purpose of this randomized controlled trial (RCT) was to evaluate the sustained effects over one year of CBT-I (Healthy Sleep: HS) compared with HF self-management education (Healthy Hearts; attention control: HH) on insomnia severity, sleep characteristics, symptoms, and function among people with stable HF. The primary outcomes were insomnia severity, actigraph-recorded sleep efficiency, and fatigue. Methods: We randomized adults with stable HF with preserved or reduced ejection fraction who had at least mild insomnia (Insomnia severity index >7) in groups to HS or HH (4 sessions/8 weeks). We obtained wrist actigraphy and measured insomnia severity, self-reported sleep characteristics, symptoms (fatigue, excessive daytime sleepiness, anxiety, depression), and six-minute walk distance at baseline, within one month of treatment, and at 6 and 12 months. We used general linear mixed models (GLMM) and generalized estimating equations (GEE) to evaluate the effects. Results: The sample included 175 participants ( M age = 63 ± 12.9 years; 43% women; 18% Black; 68% New York Heart Association Class II or II; 33%; LVEF < 45%) randomized to HS ( n = 91) or HH ( n = 84). HS had sustained effects on insomnia severity, sleep quality, self-reported sleep latency and efficiency, fatigue, excessive daytime sleepiness, and six-minute walk distance at 12 months. Conclusions: CBT-I produced sustained improvements in insomnia, fatigue, daytime sleepiness, and objectively measured physical function among adults with chronic HF, compared with a robust HF self-management program that included sleep hygiene education. Clinical Trial Information: Insomnia Self-Management in Heart Failure; https://clinicaltrials.gov/ct2/show/NCT02660385 ; NCT02660385.